Creative strategy in advertising - Drewniany, Bonnie L.; Jewler, A. Jerome (Belmont, Calif. : Wadsworth, 2014)
This book provides everything students need to be successful as advertising professionals in today's fast-changing media environment. Focusing on the idea that good advertising always starts with an understanding of people and an awareness of their needs, the text moves through the creative process step by step.
1. Creativity : unexpected but relevant selling messages -- 2. Branding : indentity and image strategy -- 3.Diversity : targeting an ever-changing marketplace -- 4. Fact finding : the basis for effective creative work -- 5. Strategy : a road map for the creative team -- 6. Ideas : the currency of the 21st century -- 7. Words on paper : connecting to consumers' hearts and minds -- 8. Layouts : designing to communicate -- 9. Radio : can you see what I'm saying? -- 10. Television : the power of sight, sound, and motion -- 11. Direct marketing : the convenience of shopping at home -- 12. The internet : the ultimate direct -- 13. Integrated marketing and communications : building strong relationships between the brand and the customer -- 14. Client pitches : how to sell your ideas.
Previous ed.: 2008.
Includes bibliographical references and index.
Media Arts
Keywords: Advertising copy; Advertising layout and typography